Judicialização de medicamentos na microrregião de saúde de Pirapora-MG - Giovana Gonçalves Pereira Cardoso (2021)
Pharmaceutical Care is comprehensive as a set of actions aimed at the promotion, protection and recovery of individual and collective health, with medication as the essential element. When people, in an attempt to guarantee access to health actions, services and supplies that are not guaranteed by the executive branch, resort to the judiciary, the judicialization of health is set up. The objective of this study was to describe the profile of lawsuits for medicines and the obligation of these decisions in relation to rename, covering the expenses arising from judicial compliance. This is a descriptive, sectional study that uses a document analysis technique and a quantitative approach. Data collection was carried out in the context of the GRS of Pirapora - MG, with a time frame from 2104 to 2019. The sample included 136 lawsuits with requests for medication requests from the State of Minas Gerais in the GRS form. A documental analysis used data available on the basis of the judicial module of the Integrated System of Management of Pharmaceutical Assistance of the State of Minas Gerais. Descriptive analysis (frequency, mean and dispersion measures), comparative analysis between groups (drugs belonging to Rename and non-Rename drugs) was performed using the chi-square test and Fisher's exact test, at a significance level of 5% and a simple linear regression between the variables number of processes and distance to the county seat municipality. There was a predominance of lawsuits filed by males over 20 years of age and residing in the municipality of Pirapora; high number of lawsuits filed between 2016 and 2018, with the majority of cases involving drugs that are not part of Rename (58.0%). Among the medicines requested belonging to the Rename, the majority (51.4%) belonged to the CEAF, and of these, 57.4% were in disagreement with the PCDT. The most requested medications were related to the central nervous system (45.2%). There were medical prescriptions from the SUS (67.2%), among which 67.8% were prescribed by the brand name, in addition to high expenses due to court decisions, in which less than 1% of the population of the health microregion of Pirapora was favored. It was concluded that there is a need to improve the dialogue between the judiciary and the health sector, qualified to make health professionals aware of adapting their practices and prescriptions to SUS regulations, in order to broaden the resolution of demands at the administrative level.